2017
DOI: 10.3102/0162373717709968
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Consequences of Excess Credit Hours Policies

Abstract: The growth of the public discourse on college completion and student debt has pushed policymakers and institutional leaders to implement a variety of policies aimed at incentivizing student completion. This article examines state-adopted excess credit hour (ECH) policies on student completion and median debt outcomes. Using a quasi-experimental approach, we find little evidence that ECH policies positively affect student completion. However, we find statistically large estimates that adoption of ECH policies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…Excess credit hour (ECH) state policies act as a "stick" incentive Daedalus, the Journal of the American Academy of Arts & Sciences Financial Constraints & Collegiate Student Learning by charging higher tuition rates for credits students take beyond a certain threshold: for example, more than 140 credits in North Carolina or more than 125 percent of the credits required for a student's degree in Virginia. 74 While intended to incentivize students to graduate quickly, ECH policies have had no effect on on-time graduation rates and have increased the amount of debt students take on, particularly for low-and middle-income students. 75 Eliminating these policies would likely alleviate the negative effects on student borrowing and could free up resources to direct to proven strategies.…”
Section: Daedalus the Journal Of The American Academy Of Arts And Sciences Financial Constraints And Collegiate Student Learningmentioning
confidence: 99%
“…Excess credit hour (ECH) state policies act as a "stick" incentive Daedalus, the Journal of the American Academy of Arts & Sciences Financial Constraints & Collegiate Student Learning by charging higher tuition rates for credits students take beyond a certain threshold: for example, more than 140 credits in North Carolina or more than 125 percent of the credits required for a student's degree in Virginia. 74 While intended to incentivize students to graduate quickly, ECH policies have had no effect on on-time graduation rates and have increased the amount of debt students take on, particularly for low-and middle-income students. 75 Eliminating these policies would likely alleviate the negative effects on student borrowing and could free up resources to direct to proven strategies.…”
Section: Daedalus the Journal Of The American Academy Of Arts And Sciences Financial Constraints And Collegiate Student Learningmentioning
confidence: 99%
“…Similarly, Garibaldi et al (2012) found that students who faced the threat of having to pay higher tuition fees after their expected graduation year were more likely to graduate on time than students who did not face the same threat of higher tuition fees. On the other hand, Kramer, Holcomb, and Kelchen (2018) found no positive impact of ECH policies on degree completion or time-to-degree. Instead, they found the median loan burden of students increased, indicating that the cost of ECH is merely shifted from the state to the student.…”
Section: Related Literaturementioning
confidence: 69%
“…Internationally, there exists a variety of policies that aim at increasing completion rates and reducing time to degree. Among these policies are merit-based aid programs, where renewal of student aid is tied to credit accumulation (such as in Scott-Clayton 2011), excess credit hour (ECH) policies, which are designed to discourage students from completing excess credits by increasing the cost of delaying graduation (see, e.g., Heineck, Kifmann, and Lorenz 2006;Kramer, Holcomb, and Kelchen 2018), and different programs that offer financial aid and/or study services in order to improve student performance (Angrist, Lang, and Oreopoulos 2009;Bettinger and Baker 2014). Consequently, there is a rich literature that studies how financial incentives can be used to improve the educational outcomes of students.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A key factor in the time it takes to earn a baccalaureate degree is the amount of excess credits (i.e., credits in excess of the requirement for a baccalaureate degree, typically 120) that a student might accumulate over their educational journey. While the knowledge gained from a course not needed for graduation may be beneficial to the student in more abstract ways, each course taken that does not directly contribute to the earning of a baccalaureate degree results in extra time (Fink et al, 2018) and money (Kramer et al, 2018;Ziedenberg, 2015) to the overall cost of education. Students who take the transfer path from a community college to a university experience such excess credit accumulation disproportionately from those who start and end at a university (Fink et al, 2018).…”
Section: Research On Articulation Agreementsmentioning
confidence: 99%